European Traffic Connections and Croatia - Vuković, Ivan; Vizjak, Ana (Promet - Traffic&Transportation, 2012)
The overall traffic connections within Europe are particularlyimportant from the economic point of view of eve1y Europeancountry. Therefore, the development of traffic and trafficinfrastructure in the European Union are considered with specialattention. The main aim of traffic development in the EuropeanUnion is full possible freedom of movement both fromthe technical and organisational aspect, with continuous improvementin traffic safety and environmental protection.Traffic development and connections are one of the essentieddevelopment factors of eve1y modem counlly. Every COU/1-try tends to organise traffic system in the way that suits her best.The same holds for the European Union as well. The leadingbodies in the European Union agree that the EU traffic systemneeds to be set upon such fundamentals that it can follow furtherdevelopment of the community. EU connects 15 membercountries into a single community, and it also plans soon to expandonto new members.The aims set by the Maastricht Agreement have been realisedby announcing the traffic guidelines on infrastructure projectsthat should be realised. In the Commission's proposal tothe Council and the Parliament in 1994, on the development ofTrans-European traffic networks, a ve1y efficient plan was presentedof connecting national traffic networks into a singleTrans-European network, to be realised until 2010.Overall economic and political connections of the EuropeanUnion and the countries in transition are becoming strongereve1y day. Several countries in transition are already preparingfor joining the European Union. This brings to the fore theneed for better traffic connections of EU and the countries intransition.In some sections the adopted Crete corridors pass alsothrough Croatia. Moreover, Croatia is located on the main Europeantraffic routes from the North to the South, and from theEast to the West.